2012
DOI: 10.4038/jccpsl.v17i1.4930
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and correlates of Body Mass Index in the elderly residents of the Colombo District

Abstract: Objective:To determine the distribution and correlates of body mass index in the elderly residents of the Colombo District. Methodology:The sample consisted of 452 subjects aged 60 years and above residing in the Colombo district of Sri Lanka. Data collection included a physical examination and an interviewer administered questionnaire. Results:The mean BMI was significantly higher in females and the 60-70 year olds compared to males and >70 year olds. Of the sample, 46% was normal weight while 20, 16 and 18% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We found that the prevalence of undernutrition among the older people as 35.3% using composite criterion. In contrast, other studies which used BMI alone showed varying estimates ranging from 20% to 39% [11,13]. Prevalence of undernutrition using the MNA tool, which assesses undernutrition based on anthropometry, recent weight loss, reduced mobility, decrease in food intake and acute disease or psychological stress over the past three months, also appears to underestimate the prevalence in Asia relative to the The current study identified a number of key factors associated with having a significant inverse association with low muscle mass in men, which included, age ≥ 70 years, no school education or up to grade 5, presence of diabetes, disability in vision, little or no responsibility in food shopping and not getting nutritional advice from media.…”
Section: Prevalence Of Undernutrition In Sri Lankamentioning
confidence: 83%
See 4 more Smart Citations
“…We found that the prevalence of undernutrition among the older people as 35.3% using composite criterion. In contrast, other studies which used BMI alone showed varying estimates ranging from 20% to 39% [11,13]. Prevalence of undernutrition using the MNA tool, which assesses undernutrition based on anthropometry, recent weight loss, reduced mobility, decrease in food intake and acute disease or psychological stress over the past three months, also appears to underestimate the prevalence in Asia relative to the The current study identified a number of key factors associated with having a significant inverse association with low muscle mass in men, which included, age ≥ 70 years, no school education or up to grade 5, presence of diabetes, disability in vision, little or no responsibility in food shopping and not getting nutritional advice from media.…”
Section: Prevalence Of Undernutrition In Sri Lankamentioning
confidence: 83%
“…We found that the prevalence of undernutrition among the older people as 35.3% using composite criterion. In contrast, other studies which used BMI alone showed varying estimates ranging from 20% to 39% [ 11 , 13 ]. Prevalence of undernutrition using the MNA tool, which assesses undernutrition based on anthropometry, recent weight loss, reduced mobility, decrease in food intake and acute disease or psychological stress over the past three months, also appears to underestimate the prevalence in Asia relative to the current study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations